Why, by Whom and How? Representations of gambling problems and their solutions in Swedish general administrative court cases - Korfitsen, Johanna; Samuelsson, Eva; Forsström, David; Cisneros Örnberg, Jenny (Critical Gambling Studies)

(untitled) (University of Alberta Library, 2025)
To strengthen the right to support for people with gambling problems in Sweden, legislative changes were enacted in 2018. This study aims to critically examine how problems and solutions are represented in 69 appeals concerning gambling treatment within the general administrative court (2014–2022) and to assess how these representations have evolved following the legal amendments. The study employs Bacchi’s WPR approach to scrutinize court judgments. The results reveal that gambling problems are unequivocally recognized as severe issues requiring intervention, with both explicit and implicit notions of the problem rooted in the concept of loss of control. Prior to the legal amendments, rulings primarily focused on identifying the responsible actor for providing care, often framed within a medical discourse. Post-amendment, the focus shifted to how treatment needs should be met, emphasizing an evidence-based discourse. These varying representations produce discursive, subjectifying, and material consequences, significantly affecting access to different welfare interventions. The new legislation has solidified the responsibility of social services to provide treatment for gambling problems. However, as the study demonstrates, responsibilization of gamblers occurs not only in policy and treatment frameworks, but also within the court system.